2015
DOI: 10.3892/br.2015.470
|View full text |Cite
|
Sign up to set email alerts
|

Auricularia auricular-judae polysaccharide attenuates lipopolysaccharide-induced acute lung injury by inhibiting oxidative stress and inflammation

Abstract: Abstract. Auricularia auricular-judae polysaccharide (AAP) has shown a variety of pharmacological properties. In the present study, the role of AAP in acute lung injury (ALI) induced by lipopolysaccharide (LPS) was analyzed in rats to further explore the possible underlying mechanisms. Adult Sprague-Dawley rats were randomly assigned into the control, AAP, LPS and LPS plus AAP groups. Rats were injected with LPS (10 mg/kg, intraperitoneal) to induce ALI. Rats in the LPS plus AAP group were treated with AAP for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…Previous studies have demonstrated that, in sustained diabetes, states of hyperglycemia and oxidative stress in vivo, and non-enzymatic glycation (glycosylation) reactions are evident, which are important in the pathogenesis of diabetes and nephropathy (3)(4)(5)(6). Jin et al reported that C-type natriuretic peptide ameliorates IRI-induced acute kidney injury through the inhibition of oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that, in sustained diabetes, states of hyperglycemia and oxidative stress in vivo, and non-enzymatic glycation (glycosylation) reactions are evident, which are important in the pathogenesis of diabetes and nephropathy (3)(4)(5)(6). Jin et al reported that C-type natriuretic peptide ameliorates IRI-induced acute kidney injury through the inhibition of oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%
“…Scavengers of ROS like ascorbic acid fortunately have the ability to reduce pulmonary hypertension, hypoxia and increased microvascular permeability, which characterize ALI following infusion of endotoxin. 5,37…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble polysaccharide (AAP I-a) isolated from Auricularia auricular prevents oxidative stress in d-galactose-induced aged mice. A paste of polysaccharides is used for the production of antiaging creams or lotions and other skin-related cosmetics in the industry (Zhang et al 2011). These polysaccharides (AAP I-a) have the ability to delay ageing as they result in the inhibition of the functional enzymes responsible for skin ageing, such as elastase, tyrosinase, hyaluronidase and MMP-1 enzymes.…”
Section: Anti-ageing Property Of Mushroommentioning
confidence: 99%
“…1.7 -Anti-ageing Zhang et al (2011) and Hung and Nhi (2012) 12 Lentinus 26.3 65.1 2.3 -Anticancer, immunomodulatory Lovy et al (1999), Gunawardena et al (2014) and Hung and Nhi (2012) 13 Cordyceps 21.9…”
Section: Introductionmentioning
confidence: 99%